2004
DOI: 10.1002/bdra.20053
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of the forebrain with radial limb defects: Garcia‐Lurie‐Steinfeld syndrome?

Abstract: In our cases and in the literature there is significant clinical overlap between Steinfeld syndrome and GLS. We propose these conditions may not be nosologically or etiologically distinct. The spectrum of severe forebrain anomalies in these conditions is broader than previously thought and may include some neural tube defects. Mild cases are difficult to identify and the full range of expression remains unknown. Autosomal dominant inheritance with incomplete penetrance and frequent new mutations is postulated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Guala et al discuss a case of possible XK aprosencephaly syndrome/Garcia–Lurie syndrome (OMIM 207770) with stenotic anus, genital anomalies and a ring‐chromosome 13 with effectively a 13q32 deletion [Guala et al, 1997]. McPherson et al [2004] reviewed this syndrome and the possibly overlapping Steinfeld syndrome (OMIM 184705) and showed that several cases have significant overlap with the 13q deletion syndrome including anogenital abnormalities. An interesting case with DK phocomelia syndrome (OMIM 223340) and anterior displacement of the anus was shown to have mosaicism for a 13q deletion (del13q12qter), with the deletion only present in fibroblasts [Bamforth and Lin, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Guala et al discuss a case of possible XK aprosencephaly syndrome/Garcia–Lurie syndrome (OMIM 207770) with stenotic anus, genital anomalies and a ring‐chromosome 13 with effectively a 13q32 deletion [Guala et al, 1997]. McPherson et al [2004] reviewed this syndrome and the possibly overlapping Steinfeld syndrome (OMIM 184705) and showed that several cases have significant overlap with the 13q deletion syndrome including anogenital abnormalities. An interesting case with DK phocomelia syndrome (OMIM 223340) and anterior displacement of the anus was shown to have mosaicism for a 13q deletion (del13q12qter), with the deletion only present in fibroblasts [Bamforth and Lin, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…(2004) the postulated autosomal recessive inheritance of GLS is not convincing because sporadic cases could represent new mutations and the two familial cases of intermediate severity could also be explained by gonadal mosaicism or incomplete penetrance. McPherson et al. (2004) supported the hypothesis that GLS and Steinfeld syndrome may represent differing severity of the same autosomal dominant condition, which could be termed Garcia‐Lurie‐Steinfeld syndrome.…”
Section: Discussionmentioning
confidence: 65%
“…Review of the literature as well as our patient suggest that Steinfeld syndrome and GLS may differ primarily in severity of brain malformation with more severe brain defects in the second condition, including anencephaly, as in our case. As already suggested by McPherson et al (2004) the postulated autosomal recessive inheritance of GLS is not convincing because sporadic cases could represent new mutations and the two familial cases of intermediate severity could also be explained by gonadal mosaicism or incomplete penetrance. McPherson et al (2004) supported the hypothesis that GLS and Steinfeld syndrome may represent differing severity of the same autosomal dominant condition, which could be termed Garcia-Lurie-Steinfeld syndrome.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Those cases with ear anomalies are consequently designated as an otocephalic phenotype with synonyms such as synotia or agnathia. 8 In addition, there may be extracranial anomalies of the reproductive tract or limbs, 21 which were not found in the lamb of this case.…”
Section: Discussionmentioning
confidence: 98%